2001
DOI: 10.1021/ja0110269
|View full text |Cite
|
Sign up to set email alerts
|

A Plethora of Carbene Interconversions on the C5H4S Energy Surface:  A Computational Study

Abstract: The potential energy surface for the reaction of atomic carbon with thiophene has been studied computationally. Intermediates which are energetically viable include the 2- and 3-thienylcarbenes 8 and 11, thiacyclohexa-3,5-dien-2-ylidene, 10, and thiacyclohexa-2,3,5-triene, 6. In accord with experimental data, 6 and 8 are in equilibrium. The lowest-energy pathway for rearrangement of 6 to 8, which is endothermic by 14.5 kcal/mol, involves ring opening to Z-2-penten-4-ynthial which then recloses to carbene 8. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Attempts to locate electronic minima for related products with pyrrole, furan and thiophene were unsuccessful. Pyrrole, furan and thiophene formed carbenes analogous those reported by Shevlin et al [1] (see ESI). Details of the properties of these systems are beyond the scope of this study and will be reported on separately.…”
Section: Tablesupporting
confidence: 82%
See 3 more Smart Citations
“…Attempts to locate electronic minima for related products with pyrrole, furan and thiophene were unsuccessful. Pyrrole, furan and thiophene formed carbenes analogous those reported by Shevlin et al [1] (see ESI). Details of the properties of these systems are beyond the scope of this study and will be reported on separately.…”
Section: Tablesupporting
confidence: 82%
“…These structures are likely to be kinetically reactive as shown by Shevlin, et al [1]. They may provide a missing link in the proposed mechanisms of reactions of atomic carbon with thiophene reported by Shevlin and co-workers [1] and may lay on the energy surface of C 6 H 5 intermediates leading to benzynes [2,3]. Future studies will focus on detailed studies of possible rearrangements and related compounds formed between heteroatoms and a variety of p systems.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Such an explanation would also seem to be at odds with the relatively high thermal barrier (>30 kcal/mol) separating singlet 3-thienylcarbene ( 13 ) and α -thial-methylenecyclopropene ( 9 ). 24 The more likely explanation, therefore, involves the excited state of the diazo compound. As observed in several other systems, 45,46 the excited state of diazo compound 1 may partition between two pathways: N 2 loss, to give 3-thienylcarbene ( 13 ), and N 2 loss with concomitant rearrangement, to give α -thial-methylenecyclopropene ( 9 ) without the intervention of the carbene.…”
Section: Resultsmentioning
confidence: 99%